Recent climate warming and the Varas rock glacier activity, Cordillera Oriental, Central Andes of Argentina - Martini, Mateo Antonio; STRELIN, Jorge Adrián; Flores, Eliseo; Astini, Ricardo Alfredo; Kaplan, Michael R. (GeoResJ)
Recent studies have revealed that in high-altitude mountain environments the global warming trend over the last few decades tends to be strongly amplified. However, few attempts have been made to monitor the possible effects of such climate changes on high-altitude rock glaciers. In this paper, we provide a geomorphic analysis of the Varas rock glacier, and present the first observations of rock glacier temperature (air and ground) and surface velocities in the Andes of northwestern Argentina. A network of 30 boulders was monitored every year between 2012 and 2016 using a differential Global Positioning System. Over the observational period, the Varas active rock glacier registered velocities between 125 and 5 cm/yr, except for four boulders which did not shift. Over the five years of monitoring, the mean annual air and ground (at 5 and 50 cm depth) temperature remained above 0 °C. A long-term instrumental weather dataset (106 years), located ∼130 km from the Varas rock glacier, at La Quiaca station, reveals a warming trend of 0.8 °C during the last century, with a steep increase during the last two and half decades. The warming trend recorded in the region may have produced or facilitated the inactivity of the more-exposed sectors of the Varas active rock glacier. However, there also may be a delay in the relatively slow and full response of rock glaciers to the last few decades of warming. Finally, the observations allow us to propose a formation sequence in the Varas rock glacier valley, since postglacial time. Fil: Martini, Mateo Antonio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: STRELIN, Jorge Adrián. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en ...